Peter Adamson, Medieval Philosophy: A History of Philosophy Without Any Gaps, Volume 4, New York: Oxford University Press, 2019, 672 pp. ISBN-10: 0198842406 ISBN-13: 978-0198842408 - Ernesto Priani Saisó (Medievalia, 2022)
.